Singing the same tune?: international continuities and discontinuities in how police talk about using force - Waddington, Peter A. J. (Crime, law and social change, 2009)
This article focuses on a research project conducted in six jurisdictions: England, The Netherlands, Germany, Australia, Venezuela, and Brazil. These societies are very different ethnically, socially, politically, economically, historically and have wildly different levels of crime. Their policing arrangements also differ significantly: how they are organised; how their officers are equipped and trained; what routine operating procedures they employ; whether they are armed; and much else besides. Most relevant for this research, they represent policing systems with wildly different levels of police shootings, Police in the two Latin American countries represented here have a justified reputation for the frequency with which they shoot people, whereas at the other extreme the police in England do not routinely carry firearms and rarely shoot anyone. To probe whether these differences are reflected in the way that officers talk about the use of force, police officers in these different jurisdictions were invited to discuss in focus groups a scenario in which police are thwarted in their attempt to arrest two youths (one of whom is a known local criminal) by the youths driving off with the police in pursuit, and concludes with the youths crashing their car and escaping in apparent possession of a gun, It might be expected that focus groups would prove starkly different, and indeed they were, but not in the way that might be expected. There was little difference in affirmation of normative and legal standards regarding the use of force. It was in how officers in different jurisdictions envisaged the circumstances in which the scenario took place that led Latin American officers to anticipate that they would shoot the suspects, whereas officers in the other jurisdictions had little expectation that they would open fire in the conditions as they imagined them to be.